PEMETAAN MAJALAH ILMIAH TERBITAN INDONESIA - Tambunan, Kamariah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2014)
This study is to find out the mapping of scientific journals published in Indonesia, mainly cover of subject, city ofpublication, publisher, period and year of publication. Directory of Indonesian Learned Periodicals which publishedby the Centre for Scientific Documentation and Information- Indonesian Institute of Sciences in year of 2004 is usedas data source. The study found that the directory are covers 1.170 journals that already have ISSN and still issueduntil year of 2003. The most subject available is technology (418 titles). The most scientific journal was published inDKI Jakarta (182 titles), then West Java (176 titles) and East Java (174 titles). The journals issued mainly by educationalinstitutions (academy, universities, schools, etc.). The journals issued half-yearly are the most common, thereare 673 titles. These journals issued in 50’s up to 2004 and the most ones (605 titles) issued in 2000-2004.